Analysis Of Aquifer Characteristics Using The Method Cooper Jacob At Block X Pt. Geomine Bara Studio Site Kutai Kartanegara, East Kalimantan, Indonesia - Sari, Avellyn Shinthya; Wardana, Novandri Kusuma; Cahyono, Yudho Dwi Galih; Sarastika, Ristya Mahda (UIR PRESS, 2025)
Using the Cooper-Jacob method, this research analyzes the characteristics of the aquifer in Block X of Geomine Bara Studio Site Ltd., Kutai Kartanegara. This method can determine the main hydrogeological parameters, such as the aquifer's hydraulic conductivity/permeability coefficient, transmissivity, and storage coefficient (storativity) of the aquifer. Data from the pumping test served to understand the aquifer's response to pumping. The research results showed that the aquifer in Block X had a transmissivity of 193,9949 m²/day, hydraulic conductivity of 6,0634335 m/day, and a storage coefficient (storativity) of 0,000137. The soil type at the test location was fine sandy with a low porosity value of n = 0,499%, and the soil permeability was low at k = 0,056403975 mm/ sec. Groundwater in the study area had quite potential for meeting the needs of Geomine Bara Studio Site Ltd in Kutai, Kartanegara, with a groundwater availability of H219,398 m³ and a withdrawal rate of Q 182,0678 m³/day. This study indicated high water flow capacity with low storage ability, suggesting a confined aquifer. It benefits sustainable groundwater management and mitigates environmental impacts in the study area.